The geometric supposer : what is it a case of? - Schwartz, Judah L., 1934-; Yerushalmy, Michal; Wilson, Beth (Technology in education series., 1993)
The Geometric Supposer encourages a belief in a better tomorrow for schools. On its surface, the Geometric Supposer provides the means for radically altering the way in which geometry is taught and the quality of learning that can be achieved.